Aplicações do óleo essencial de aloysia citriodora paláu e do citral adicionados à água e à dieta para jundiá e carpa-capim - Santos, Alessandro Casale dos (2020)
The present study deals with the effectiveness of citral added to water as a sedative and anesthetic in silver catfish (Rhamdia quelen) and grass carp (Ctenopharyngodon idella). It deals with the anesthetic safety of the essential oil (EO) of Aloysia. citriodora Paláu and citral in jundiá. In addition, it deals with the protective effect of OE of A. citriodora added to the jundiá diet against the experimental inoculation of Aeromonas hydrophila. Although A. citriodora EO has already proven its sedative and anesthetic efficacy in fish, this is the first report of the citral as sedative and anesthetic in silver catfish and grass carp. The sedative and anesthetic efficacy of citral was confirmed by checking the time elapsed for inducing sedation and anesthesia and, recovering from anesthesia, using different concentrations of the substance. In addition, based on the determination of the minimum effective concentration capable of achieving the maximum effect observed, the ideal concentration for inducing rapid anesthesia in both species was verified. The safety of anesthetic procedures induced by the EO of A. citriodora and citral was verified to maintenance of anesthesia for 10 min in silver catfish. Anesthesia was induced from the concentration capable of reaching the level of effect immediately prior to the maximum effect observed, and maintenance was performed from the minimum concentration capable of inducing anesthesia, within the maximum proposed period of 30 min. For this, data on mortality were verified, in addition to hematological and biochemical determinations, after the procedures. The efficacy of different doses of EO of A. citriodora in protecting silver catfish against experimental inoculation by A. hydrophila was verified from data on mortality, in addition to hematological and biochemical determinations. Citral was effective in inducing sedation in silver catfish and grass carp in concentrations ranging from 15 to 40 μL L-1 and, anesthesia without mortality in concentrations ranging from 50 to 600 μL L-1 in silver catfish and 75 to 450 μL L-1 in grass carp. Mortality was verified in the concentrations of 675 and 600 μL L-1 in jundiá and grass carp, respectively. The ideal concentration for the induction of rapid anesthesia was 300 μL L-1 in both species. The EO of A. citriodora and citral were safe in inducing and maintaining anesthesia in silver catfish from concentrations of 225 μL L-1 for induction and 50 μL L-1 for maintenance. There was no mortality in maintaining anesthesia, and the only determined parameter that showed variation was the mean corpuscular hemoglobin concentration (CHCM), which varied according to the different groups formed and the moments of collection. The OE of A. citriodora possibly protected silver catfish against experimental inoculation by A. hydrophila at a dose of 2 ml Kg-1. Therefore, the EO of A. citriodora and citral are substances with potential use in fish farming as sedatives and anesthetics, and the OE of A. citriodora to protect against infection by A. hydrophila.